Warunki praktykowania edukacji domowej w Polsce - Giercarz-Borkowska, Magdalena (Kultura-Społeczeństwo-Edukacja, 2021)
The article concerns the subject of homeschooling practice conditions in Poland – it focuses on the legal conditions and outlines the socio-economic conditions in which Polish homeschoolers operate. It discusses the specific kind of right which is the right to education, its position in the systematics of the constitution and the connection to the learning duty and school duty. It brings attention to state-citizen relations and the rule of state subsidiarity. It points to legal regulations which allow realization of the school duty outside of school, underlining the controversial and discriminatory regulations which ignore the parents’ priority to decide on their own children’s education and treat children learning in this way unequally to those who attend school. The article is ended by an observation about the state remaining decisive on the form of education of each citizen, despite the constant change of legal regulations, which in relation to the discussed subject characterizes the last three decades.